2018
DOI: 10.1186/s41039-018-0070-3
|View full text |Cite
|
Sign up to set email alerts
|

Using design-based research to develop a Mobile Learning Framework for Assessment Feedback

Abstract: Students’ lack of engagement with their assessment feedback and the lack of dialogue and communication for feedback are some of the issues that affect educational institutions. Despite the affordance that mobile technologies could bring in terms of assessment feedback, research in this area is scarce. The main obstacle for research on mobile learning assessment feedback is the lack of a cohesive and unified mobile learning framework. This paper thus presents a Mobile Learning Framework for Assessment Feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 55 publications
1
36
0
1
Order By: Relevance
“…Our results agree with the findings in the literature (Bikanga-Ada, 2018;Lestari et al, 2017;Mohamad, 2012;Popenici & Kerr, 2017;Tarpin-Bernard & Habieb-Mammar, 2005;Techataweewan, 2010;Tsoulouhas et al, 2012;Wang et al, 2019) which found that adaptive hypermedia techniques have a positive effects on improving the student' learning outcomes. Nevertheless, it differs with Ross et al (2018) that showed no improvement in students' learning outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with the findings in the literature (Bikanga-Ada, 2018;Lestari et al, 2017;Mohamad, 2012;Popenici & Kerr, 2017;Tarpin-Bernard & Habieb-Mammar, 2005;Techataweewan, 2010;Tsoulouhas et al, 2012;Wang et al, 2019) which found that adaptive hypermedia techniques have a positive effects on improving the student' learning outcomes. Nevertheless, it differs with Ross et al (2018) that showed no improvement in students' learning outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…While these five phases are listed separately, it is important to note that they are highly interconnected. Despite the relevance of the evaluation phase (Ada 2018), few frameworks considered evaluation as part of the learning design or pedagogical activity aimed at monitoring and evaluating learning progress and outcomes. Leaders, teachers, learners, families, and community members have been identified as the key pillars who uphold and maximize mobile learning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…5 shows the third phase of the framework. Rikala (2015) Vision as ubiquitous knowledge construction Brummelhuis and van Amerongen (2011) Vision as ubiquitous knowledge construction and values Peng et al (2009) Values (communication, collaboration, and culture) and learning objectives, learning outcomes, and learning progress Ada (2018) Values (culture, standards, collaboration; creativity) and purpose of the study Crompton (2017), Hwang (2014), Liu et al (2008) and Park (2011)…”
Section: Strategic Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Education in developing countries could be transformed and benefit from ICT4D strategies such as mobile technology (Badar, et al, 2018). With mobile-learning, learners have more flexibility of what, when, where, why and how to learn, making it an individualized, personalized and highly interactive learning (Bikanga Ada, 2018;Khaddage, Muller, & Flintoff, 2016;Cobcraft, Towers, Smith, & Bruns, 2006). Mobile phones are widely considered as the optimal solution for delivering education in developing countries, because of their usability, accessibility, and affordability (Grimus, et al, 2013;Ford & Leinonen, 2009).…”
Section: Introductionmentioning
confidence: 99%